2022
DOI: 10.1097/rct.0000000000001347
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Computed Tomography Image Reconstruction for Improving Visualization of Pulmonary Vasculature: Comparison Between Preprocessing and Postprocessing Images Using a Contrast Enhancement Boost Technique

Abstract: ObjectiveThis study aimed to evaluate chest computed tomography (CT) angiography image quality using the contrast enhancement (CE)–boost technique compared with conventional images.MethodsForty patients who underwent contrast-enhanced chest CT were included. Combined CT angiography images of the iodinated image obtained from the subtraction of nonenhanced CT images and CT angiography images were used to generate CE-boost images. Computed tomography attenuation, signal-to-noise ratio (SNR), and contrast-to-nois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Additionally, because of the integrated denoising filter, the dark-blood technique maintained image noise even with the subtraction and addition operations. Our method is an extension of the contrast-enhancement boost (CE-boost) technique, which has traditionally been utilized to further increase enhancement on contrast-enhanced CT for various body parts [ 19 20 21 ]. The CE-boost technique was modified to generate dark-blood CT images in which the paired arterial and delayed-phases served as inputs instead of the conventional pair of unenhanced and enhanced images.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, because of the integrated denoising filter, the dark-blood technique maintained image noise even with the subtraction and addition operations. Our method is an extension of the contrast-enhancement boost (CE-boost) technique, which has traditionally been utilized to further increase enhancement on contrast-enhanced CT for various body parts [ 19 20 21 ]. The CE-boost technique was modified to generate dark-blood CT images in which the paired arterial and delayed-phases served as inputs instead of the conventional pair of unenhanced and enhanced images.…”
Section: Discussionmentioning
confidence: 99%
“…The CE-boost technique shows promise in reducing the amount of contrast media and improving radiologists’ diagnostic confidence. Previous studies have demonstrated that the application of CE-boost significantly improves the detection of type II endoleaks following endovascular aortic aneurysm repair [ 7 ], shows efficacy in visualizing smaller diameter abdominal arteries and portal veins [ 9 , 10 ] and peripheral pulmonary arteries [ 8 ]. In the present research, the CE-boost images exhibited improved visibility of the veins compared to the original images.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a noise-reduced iodine image is obtained through a noise-reduction procedure applied to the subtracted iodine image. Finally, a CE-enhanced image is created by adding the noise-reduced image to the original contrast-enhanced image using an automated process of pixel alignment [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%